2004
DOI: 10.1121/1.1778903
|View full text |Cite
|
Sign up to set email alerts
|

Auditory stream segregation in monkey auditory cortex: effects of frequency separation, presentation rate, and tone duration

Abstract: Auditory stream segregation refers to the organization of sequential sounds into "perceptual streams" reflecting individual environmental sound sources. In the present study, sequences of alternating high and low tones, "...ABAB...," similar to those used in psychoacoustic experiments on stream segregation, were presented to awake monkeys while neural activity was recorded in primary auditory cortex (A1). Tone frequency separation (AF), tone presentation rate (PR), and tone duration (TD) were systematically va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
180
5
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(214 citation statements)
references
References 81 publications
28
180
5
1
Order By: Relevance
“…Microelectrode studies in animals provide clear evidence for forward suppression at a neuronal level in auditory cortex (Calford and Semple, 1995;Brosch and Schreiner, 1997;Fishman et al, 2001Fishman et al, , 2004Kanwal et al, 2003;Ulanovsky et al, 2003;Klump, 2004, 2005;Wehr and Zador, 2005). Much of the data illustrates frequency-dependent suppression, with a greater effect of one tone on subsequent ones when the tones are close in frequency than when they are far apart.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microelectrode studies in animals provide clear evidence for forward suppression at a neuronal level in auditory cortex (Calford and Semple, 1995;Brosch and Schreiner, 1997;Fishman et al, 2001Fishman et al, , 2004Kanwal et al, 2003;Ulanovsky et al, 2003;Klump, 2004, 2005;Wehr and Zador, 2005). Much of the data illustrates frequency-dependent suppression, with a greater effect of one tone on subsequent ones when the tones are close in frequency than when they are far apart.…”
Section: Discussionmentioning
confidence: 99%
“…The present findings indicate a more broadly distributed sensitivity to f 0 that may reflect neuronal sensitivity to the differing temporal properties of tones of different f 0 , rather than a sensitivity to pitch per se. Frequency-selective forward suppression of neural responses in the auditory cortex (or the equivalent in nonmammalian species) has been proposed to play an essential role in auditory streaming (Fishman et al, 2001(Fishman et al, , 2004Kanwal et al, 2003;Klump, 2004, 2005;Micheyl et al, 2005Micheyl et al, , 2007. Specifically, it has been suggested that whether a sequence of pure tones is perceived as a single coherent stream or as two separate streams depends on the degree to which one tone influences the responses to subsequent tones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, links between same-feature events are established first, because the reduction of link strength between adjacent sounds owing to high feature separation (e.g. by topological distance in a tonotopically organized area of the auditory cortex; [60,61]) exceeds that caused by longer temporal separation between the non-adjacent (but same feature) sounds. In other words, the cost of establishing the link between topologically highly separate focuses of neural activity exceeds that of establishing the link between the neural activity elicited by the incoming sound and a relatively more decayed neural after-effect of the previous (less recent) same-feature sound.…”
Section: The Time Course Of Sequential Group Formationmentioning
confidence: 99%
“…The context, or environment surrounding a probe tone, modulates the amplitude of both single-and multi-unit neural activity. Contextual factors such as temporal sound density (Blake and Merzinich, 2002;Brosch and Schreiner, 2000), temporal onset time (Steinschneider et al, 2005), interaural phase disparity (Malone et al, 2002), or forward (Brosch and Schreiner, 1997;Fishman et al, 2004) and backward (Brosch et al, 1998) masking, arising from properties of adjacent sounds, have been shown to influence the way that auditory cortical neurons respond to the probe tone. What is unique in the current study is that the cortically generated response to the probe tone was modified by sounds not in its immediate proximity.…”
Section: Context-dependent Encoding Of Auditory Information In Auditomentioning
confidence: 99%